Analysis of immunogenetics interlaboratory comparisons’ success rates. External quality assurance system of the Spanish Society for Immunology GECLID-SEI - Martín, M. Carmen (Frontiers in Genetics, 2024)
Background: For many years, transplantation outcome was uncertain and not hopeful, until histocompatibility testing spread. Common criteria for histocompatibility assays and communications' improvement allowed an efficient organ sharing system. The possibility of organ exchanges is closely linked to the importance of interlaboratory comparisons for histocompatibility and immunogenetics methods. The External Proficiency Testing (EPT) systems are the most powerful quality assurance tools. They help achieve harmonization of analyses, set a standard of performance and a common interpretation. Methods: The External Quality Assurance program for Diagnostic Immunology Laboratories (Garantía Externa de Calidad para Laboratorios de Inmunología Diagnóstica, GECLID) program runs nowadays 13 external quality assurance (EQA) Histocompatibility & Immunogenetics schemes, the first of them from 2011 to date: serological and molecular: low and high resolution Human Leukocyte Antigen (HLA), Human Platelet Antigen (HPA) and Killer Inhibitory Receptor (KIR) typing, HLA-B*27, HLA-B*57:01 and coeliac disease-related HLA), cell dependent cytotoxicity (CDC) and flow cytometry (FC) crossmatches, anti-HLA and anti-HPA antibodies and chimerism. Results: A total of 85 laboratories participated in this subprogram in the last 12 years reporting over 1.69M results, 1.46M for anti-HLA and anti-HPA antibodies, 203.810 molecular typing data (HLA, HPA and KIR genes), 2.372 for chimerism analyses and 39.352 for crossmatches. Based on the European Federation for Immunogenetics (EFI) standards for EPT providers, the mean success rates ranged from 99.2% for molecular typing schemes and antibodies and 94.8% for chimerism, it was 96.7% regarding crossmatches, and 98.9% in serological typing. In 2022, 61.3% of the participating laboratories successfully passed every HLA EQA scheme, although 87.9% annual reports were satisfactory. Most penalties were due to nomenclature errors or misreporting of risk associated to HLA and disease. Conclusions: This EQA confirms the reliability of HLA and Immunogenetics assays in routine care. There is little heterogeneity of results of different assays used by participating laboratories, even when in house assays are used. Reliability of test results is reasonably granted